Replication of Bacteriophage φX174 DNA in a Temperature-Sensitive dnaE Mutant of Escherichia coli C - Dumas, Lawrence B. (1973)
Bacteriophage φX174 cannot grow in a temperature-sensitive dnaE (DNA polymerase III) mutant of Escherichia coli C at the nonpermissive temperature. The inability to grow is the result of inhibition of virus DNA synthesis. The synthesis of the parental replicative form is unaffected, but the replication of the replicative form and the synthesis of the single-stranded virus DNA are inhibited.